The Effect of Different Type of Material for Front Car Hood Panel Impact Simulation - Mohd Badli, Muhammad Faizul Amri; Wan Abdul Rahman, Wan Mohd Wardi (Progress in Engineering Application and Technology, 2021)
In this research, an analysis was conducted on the topic of crash analysis. The objective is to analyze the total deformation and equivalent stress of the front car hood panel when collision happen at different velocity with different material. The analysis will be done by doing a simulation using Ansys Workbench software. The software used for the simulation are SOLIDWORKS, Ansys Workbench and Mechanical ADPL. Type of crash test for the crash analysis is frontal impact. The subject of analysis for the simulation are front car hood panel that being designed in SOLIDWORKS and for fixed support is a rigid wall. Three type of material will be subjected to the simulation model which is structural steel, aluminium alloy and AL6061-T6. For the fixed support which is the rigid wall, concrete will be used as the general material. Various incoming speeds were considered when the front car hood front model was simulated to crash into a wall. Five different velocity will be simulated in the simulation. The velocity are 20 km/h, 40 km/h, 60 km/h, 80 km/h and 100 km/h. It can be concluded from this simulation that structural steel has the highest total deformation and equivalent stress than aluminium alloy and AL6061-T6.